By default, for a function chain, Pure grammar composer will extract the first parameter of the first function
and render it as the caller of that function rather than a parameter
e.g. fx(fy(p1, p2), p3) will be rendered as p1->fy(p2)->fx(p3) instead of fy(p1, p2)-> fx(p3)
We do a hack to get around this by setting a dummy value as the first parameter of the first function in the chain.
Then remove this dummy value from the final code.
By default, for a function chain, Pure grammar composer will extract the first parameter of the first function and render it as the caller of that function rather than a parameter e.g. fx(fy(p1, p2), p3) will be rendered as p1->fy(p2)->fx(p3) instead of fy(p1, p2)-> fx(p3)
We do a hack to get around this by setting a dummy value as the first parameter of the first function in the chain. Then remove this dummy value from the final code.